Workforce diversity: a case of discrimination at M health organization in Bengkalis, Indonesia - Hasysya, Hauriya; Fakhruddin, Faizah Mohd; Khamis, Noorzana; Mohd Fakhruddin, Fathiyah; Ahmad Tajudin, Bazlin Darina (Human Resources Management Academic Research Society (HRMARS), 2024)
Discrimination is one of the issues that can arise in an organization due to workforce diversity. This study elaborates on the issue of discrimination in terms of its various forms, factors, and possible solutions to minimize the problem. This study collects the data using the qualitative approach and the case study research design. Six informants, including two division leaders and four staff members (two female and four male employees) at the M Health Organization in Bengkalis, Indonesia, were selected for this study. The semi-structured and in-depth interviews were guided by an interview protocol devised by the researchers, which aims to answer all the research objectives related to the issue of discrimination. Thematic analysis using NVivo 12 Plus software was employed to analyze the data. The findings show that the incidence of discrimination exists in the organization in the form of gender discrimination, which is manifested in the cases of different salaries and disparate workloads. Further, the findings also show that the factor of discrimination is patriarchal culture. In terms of possible solutions suggested by the informants, the organization’s role, such as the inclusion of the employees in non-job-related activities and programs, discussion with the superiors and involved parties, and issuance of warnings and sanctions, are said to be implemented by the organization. Besides, the role of individual employees is also highlighted in having personal discussions with the parties involved, i.e., the perpetrator and the victim. Searching for organizations or companies genuinely dedicated to solving this issue should be the first step in any future investigation. This indicates that future research related to workforce diversity and discrimination in organizations is relevant for obtaining solutions to the said social phenomenon in the workplace.